AB0006 Assessment of Rheumatoid and Psoriatic Arthritis Susceptibility Loci in A Genetic Homogeneous Population of Greece. (15th July 2016) - Myrthianou, E.; Zervou, M.I.; Budu-Aggrey, A.; Eliopoulos, E.; Kougkas, N.; Kardassis, D.; Boumpas, D.T.; Barton, A.; Sidiropoulos, P.; Goulielmos, G.N.
Abstract : Background: Genome wide association studies (GWAS) have detected a considerable number of rheumatoid arthritis (RA) susceptibility loci [1]. Some RA loci have also been found to be associated with psoriatic arthritis (PsA) [2], demonstrating that there is a degree of genetic overlap between various autoimmune diseases. Objectives: We sought to investigate whether single nucleotide polymorphisms (SNPs) mapping to previously reported RA and/or PsA susceptibility loci, including PLCL2 (rs4535211), CCL21 (rs2812378), REL (rs13017599), STAT4 (rs10181656), CD226 (rs763361), PTPN22 (rs2476601) and TYK2 (rs34536443), are associated with risk for the two diseases in a genetically homogeneous Greek population. Methods: A total of 392 RA patients, 126 PsA patients and 521 healthy age and sex matched controls from Greece were included. Genotyping of the SNPs was performed with Taqman primer-probe sets, using a Real-Time PCR platform (Applied Biosystems, ViiA™ 7 Real-Time PCR System). Odds ratios (OR) and 95% confidence intervals (CI) were calculated and the statistical difference in allele distribution was assessed by means of x 2 test or Fisher's exact test. Bioinformatic analysis was performed using BlastP, Pymol and Maestro and Desmond (Schrodinger Inc.). Results: A significant association was detected between the GC genotype of rs34536443 ( TYK2 ) in both the PsA (p=0.019, OR=0.099, 95% CI 0.005–1.65) and RA cohorts (p=0.033, OR=0.33, 95% CI 0.123–0.90). The C allele of this SNP was associated with PsA only (p=0.02, OR=0.10, 95% CI 0.006–1.681). This polymorphism, located on exon 3, causes a Pro1104Ala mutation which is located at the beginning of an alpha-helical structure. Significant evidence for association with PsA was also found for the GG genotype and G allele of the rs10181656 SNP of STAT4 (p=0.04, OR=4.3, 95% CI 1.01–18.39 and p=0.03, OR=1.46, 95% CI 1.03–2.08, respectively). Bioinformatics analysis revealed that the C but not G allele of this SNP is located within a putative binding site for transcription factors Pax-4, PPAR/RXR and ZNF99. The TC genotype of the rs763361 SNP of CD226 was associated with PsA (OR=0.61, p=0.04) but no association was found with RA. This SNP, results in a Gly307Ser substitution, and is thought to be associated with the generation of a protein phosphorylation site. No association was found with the remaining four loci examined. Conclusions: Genetic overlap between PsA and RA was detected for the rs34536443 SNP of TYK2 gene within a Greek population. The Pro1104Gly mutation of TYK2 may influence its functionality by affecting structural and dynamical elements of the molecule. An association of STAT4 (rs10181656) with PsA was confirmed while CD226 (rs763361) was associated with PsA but not RA, in contrast to previous reports. The different findings of this study compared to previous ones highlights the importance of comparative studies that include various ethnic or racial populations. References: Okada et al. (2014). Nature 506:376–81 Bowes et al. (2012). Ann Rheum Dis 71:1350–4 Disclosure of Interest: None declared